2012
DOI: 10.1103/physrevb.86.165318
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic oscillations of spin current polarization in a paramagnetic resonant tunneling diode

Abstract: A spin-and time-dependent electron transport has been studied in a paramagnetic resonant tunneling diode using the self-consistent Wigner-Poisson method. Based on the calculated currentvoltage characteristics in an external magnetic field we have demonstrated that under a constant bias both the spin-up and spin-down current components exhibit the THz oscillations in two different bias voltage regimes. We have shown that the oscillations of the spin-up (down) polarized current result from the coupling between t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 48 publications
(73 reference statements)
0
26
0
1
Order By: Relevance
“…Theoretical work by several other groups predicted the same phenomenon [13][14][15][16] . It has been suggested that the RTD intrinsic current oscillations could circumvent the low-power problem and lead to THz-frequency power in the milli-watt range 12 .…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…Theoretical work by several other groups predicted the same phenomenon [13][14][15][16] . It has been suggested that the RTD intrinsic current oscillations could circumvent the low-power problem and lead to THz-frequency power in the milli-watt range 12 .…”
Section: Introductionmentioning
confidence: 66%
“…Zhao et al 17 proposed a mechanism that emphasized the importance of the formation of a quantum well on the emitter side of the device (the emitter quantum well, EQW) and connected the frequency of the oscillations to the average energy spacing between the bound states in the EQW and the main quantum well (MQW). The work of Jensen and Buo 13 and others [14][15][16]18,19 on intrinsic current oscillations focused on RTDs with a traditional doping profile (no doping in the region around the well and barriers), where the EQW only forms at low temperature (77 K or below) and in a narrow bias window. For this reason, and due to thermal broadening effects, it has been argued that intrinsic current oscillations could only occur at low temperatures 17 .…”
Section: Introductionmentioning
confidence: 99%
“…It can operate as a spin filter 51,52 in which the spin filtering operation results from the joint effect of the constriction and spin Zeeman effect controlled by the magnetic field. This operation is similar to the operation of the quantum point contacts.…”
Section: Resultsmentioning
confidence: 99%
“…The spin filter effect in a resonant tunneling diode (RTD) with paramagnetic quantum well embedded in II-VI DMS (ZnMnSe) was studied theoretically [9][10][11] and experimentally demonstrated by Slobodskyy et al 12 For the paramagnetic RTD, in the presence of the external magnetic field, the exchange interaction between the conduction band electrons and the Mn 2+ ions leads the giant Zeeman splitting 13 of the quasi-bound state in the paramagnetic quantum-well. This splitting causes that the resonance conditions for the spin up and spin down electrons are satisfied for different bias voltages leading to the separation of the spin current components and consequently to the spin polarization of the current.…”
mentioning
confidence: 99%
“…Equations (1) and the Poisson equation form the system of non-linear integro-differential equations that is solved by the self-consistent procedure. 9 After reaching convergence the spin dependent current density is calculated using the formula…”
mentioning
confidence: 99%